Edukasi Kesehatan Mental Berbasis Fenomena Kecemasan, Kesepian, dan Somatoform melalui Program “Gerakan Sadar Jiwa” di UPTD Puskesmas Marga Jaya - Almaira Aura Zahra; Anggi Khoiriyyah Putri; Fadia Ayu Sarika; Layla Putri Amalya; Marsya Amalia Syarif; Naswha Abystha; Tiara Putri Islami; Virza Ratna Diani; Zhika Nur Cahyani; Kus Hanna Rahmi (Yayasan Daarul Huda Kruengmane, 2026)
Mental health is a crucial aspect of individual and community well-being, yet it is often overlooked due to low literacy and persistent stigma. A Community Service Program (KKN) program at the Marga Jaya Community Health Center (UPTD), identified three dominant mental health phenomena in the community: anxiety, loneliness, and somatoform complaints. The anxiety and loneliness phenomena were identified through the